Religion in diverse societies: crossing the boundaries of prejudice and distrust - Kollontai, Pauline; Yore, Sue (Routledge, 2025)
Humanitas for the 21st century: the role of religion in a values-led public discourse on global challenges / Philip McDonagh -- From the mystical internal to the political external: revisiting Dorothee Soelle's Concept of mysticism and resistance as a way of moving beyond dualistic thinking / Sue Yore.